Crocodylomorph eggs and eggshells from the Lourinhã Fm. (Upper Jurassic), Portugal - Russo, João (2015)
We here present fossil crocodylomorpha eggshells from the Late Jurassic Lourinhã Formation of Portugal, recovered from five sites: one nest from Cambelas and various fragments from Casal da Rola, Paimogo I, Paimogo II, and Peralta. The nest is composed of 13 eggs and is the only sample not found in association with dinosaur egg material. Our research reveals that on a micro- and ultrastructural analysis, all our samples present the typical characters consistent with crocodiloid eggshell morphotype, such as the shell unit shape, the organization of the eggshell layers, and the triangular blocky extinction observed with crossed nicols. We assign the material from the Lourinhã Formation to the oofamily Krokolithidae, making it the oldest crocodylomorph eggs known so far, as well as the best record for eggs of non-crocodylian crocodylomorphs. Furthermore, our study indicates that the basic structure of crocodilian eggshells has remained stable since at least the Late Jurassic.